Model‐based characterization of the relationship between dapagliflozin systemic exposure and HbA1c response in patients with type 1 diabetes mellitus. Issue 6 (14th March 2019) - Parkinson, Joanna; Tang, Weifeng; Åstrand, Magnus; Melin, Johanna; Ekholm, Ella; Hamrén, Bengt; Boulton, David W.
Abstract : Aims: To quantitatively describe the relationship between dapagliflozin systemic exposure and HbA1c response among patients with type 1 diabetes mellitus (T1DM) and assess the potential impact of covariate effects. Materials and Methods: Individual longitudinal HbA1c data from two phase 3 studies in patients with T1DM (24‐week treatment with once‐daily dapagliflozin 5 or 10 mg or placebo, with adjustable insulin) were analyzed using a non‐linear mixed effect modeling approach. Area under the concentration curve was used to measure dapagliflozin systemic exposure. Baseline HbA1c, estimated glomerular filtration rate, reduction in total insulin dose, baseline glucose concentrations, age, sex, race (Asian vs. non‐Asian), and insulin administration method (multiple daily injections vs. insulin pump) were assessed as covariates. Results: A maximum effect (Emax ) model identified a positive exposure–response relationship. Model‐predicted placebo‐corrected HbA1c reductions after 24 weeks for dapagliflozin 5‐ and 10‐mg doses were − 0.42% [95% confidence interval (CI) −0.47 to −0.36) and − 0.45% (95% CI −0.50 to −0.40), respectively; baseline HbA1c was ~8.4%. This was in good agreement with actual observations from both studies. Baseline HbA1c was a significant covariate: patients with higher baseline HbA1c were predicted to have greater HbA1c reductions. Conclusions: The relationship between dapagliflozin systemic exposure and HbA1c response was successfully described in patients with T1DM. None of the tested covariates affected the efficacy of dapagliflozin to a clinically relevant extent. Therefore, no dose adjustment of dapagliflozin is required in patients with T1DM based on the tested covariates.ClinicalTrials.gov, NCT02268214; NCT02460978.